Er:YAG and Diode Lasers in Treatment of Peri-Implantitis–A Case Report - Alexandros Nikita (Journal of Clinical and Diagnostic Research, 2019)
One of the leading causes of dental implant loss in the present time is peri-implantitis. This paper describes a clinical case of peri-implantitis treatment using Er:YAG and a 980-nm diode laser. In the present case report, it is explained how to use these two different wavelengths on soft tissue and on the implant surface. The use of diode and Er:YAG lasers allows the removal of inflamed tissue and the bacterial biofilm from the implant surface which results in bone regeneration/reparation in the peri-implant area. In the present report, it is recommended using Er:YAG and diode lasers at 2W power to be used in the therapy of peri-implantitis.